2001
DOI: 10.1037/h0086892
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in adolescent girls: Implications for policy, prevention, and treatment.

Abstract: This review of literature focuses on aggression and adolescent girls. Recent official crime statistics from Statistics Canada show an increase in violent offences by girls. This statistic has created considerable interest in a heretofore largely ignored area of childhood maladjustment. Important differences regarding the development and expression of aggression with girls in contrast to boys is provided. In the context of what is acknowledged to be a limited literature, there are important themes for human ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 86 publications
(108 reference statements)
1
13
0
2
Order By: Relevance
“…Although previous research found that boys were more likely than girls to be involved in bullying situations, or that sex differences reduced when assessing indirect aggression alone (e.g., Olweus 1993;Siann et al 1994;Young and Sweeting 2004), our findings suggest that female bullies may be more prevalent than previously thought. In general, reports of female aggression appear to be on the rise in the US as well as other industrialized countries (Henington et al 1998;Leschied et al 2001). Burman et al (1998) reported that more girls than ever before were involved in the British juvenile justice system, and in the US, girls account for approximately one-third of juvenile arrests while violent offenses among girls are becoming increasingly prevalent (e.g., Budnick and Shields-Fletcher 1998;Federal Bureau of Investigation 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research found that boys were more likely than girls to be involved in bullying situations, or that sex differences reduced when assessing indirect aggression alone (e.g., Olweus 1993;Siann et al 1994;Young and Sweeting 2004), our findings suggest that female bullies may be more prevalent than previously thought. In general, reports of female aggression appear to be on the rise in the US as well as other industrialized countries (Henington et al 1998;Leschied et al 2001). Burman et al (1998) reported that more girls than ever before were involved in the British juvenile justice system, and in the US, girls account for approximately one-third of juvenile arrests while violent offenses among girls are becoming increasingly prevalent (e.g., Budnick and Shields-Fletcher 1998;Federal Bureau of Investigation 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported that rates of lying, truancy and status-type offences such as under-age drinking and sexual promiscuity increase among antisocial females relative to males (Leschied et al, 2001). Other studies have revealed no difference in types of delinquent behavior, including status offenses (Elliott, 1994;Steffensmeier and Allan, 1996).…”
Section: Are the Phenotype And Developmental Course Of Disruptive Andmentioning
confidence: 99%
“…Hostile thoughts and feelings are important precursors of more overt forms of aggression [Anderson and Bushman, 2002;Norlander and Eckhardt, 2005]. In fact, anger and hostility may be particularly good predictors of later physical aggression among women [Leschied et al, 2001]. Moreover, increased hostility predicts poorer mental, physical, and social functioning [O'Neil and Emery, 2002;Shapiro et al, 1996].…”
Section: Introductionmentioning
confidence: 99%